On Schur classes for modules over group rings - Semko, N. N.; Chupordya, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We consider the problem of the coupling between a factor-module $A / C_A(G)$ and a submodule $A(ω RG)$, where $G$ is a group, $R$ is a ring, and $A$ is an $RG$-module. It is possible to consider $C_A (G)$ as an analog of the center of the group and the submodule $A(ω RG)$ as an analog of the derived subgroup of the group.